Análise qualitativa de deformações em sólidos, por meio de monitoramento em tempo real do mapa de fases da Shearografia digital - Almeida, Thiago Paiva (2021)
With the advancement of technology, there is a need to inspect and monitor structures and composite elements in order to anticipate possible structural damage. The development of this project was based on the principle of coherent Light together with the sheargraphy technique, with the purpose of observing deformation in solids. Tests were carried out on materials such as steel, wood, nylon and acrylic as a way to validate the technique for different composites. Using a controlled environment, an interferometric system, a CCD camera and a processed system, with an HMI (Human Machine Interface), it was possible to generate the deformation maps in real time, and show at the end graphs that allow to visually identify the deformation that is happening in the specimens. In this way, this project contributes through images in three dimensions, as a complementary tool for professionals in the engineering area to use to start, from qualitative visual inspection, repair processes in possible structural damages.